1998
DOI: 10.1177/030006059802600501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an α-Glucosidase Inhibitor (Voglibose), in Combination with Sulphonylureas, on Glycaemic Control in Type 2 Diabetes Patients

Abstract: A multicentre study was conducted to evaluate the effect of the alpha-glucosidase inhibitor, voglibose, on glycaemic control in 113 patients with type 2 diabetes whose blood glucose control was poor on treatment with a sulphonylurea drug. The patients were treated for 24 weeks with 0.6 mg voglibose, given orally three times daily, before a meal, together with their usual sulphonylurea drug treatment. In the 86 patients who completed the study, fasting plasma glucose, 2-h post-prandial plasma glucose and haemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 13 publications
1
54
0
Order By: Relevance
“…They may act as inhibitors of amylase and glucosidase (similar to acarbose, miglitol and voglibose) leading to a reduction in post-prandial hyperglycemia (Bailey 2001). Synergy between phenolics and dietary fiber may play a role in mediating amylase inhibition and therefore, have the potential to contribute to the management of type II Diabetes mellitus (Saito et al 1998;Toeller 1994). Chethan et al (2008a) studied the mode of inhibition of finger millet malt amylases by the millet phenolics and reported that the crude polyphenolic extract exerts mixed non-competitive type inhibition, whereas the individual phenolic compounds isolated from the extract exhibit uncompetitive inhibition.…”
Section: Inhibition Of Malt Amylases Pancreatic Amylase Intestinal mentioning
confidence: 99%
“…They may act as inhibitors of amylase and glucosidase (similar to acarbose, miglitol and voglibose) leading to a reduction in post-prandial hyperglycemia (Bailey 2001). Synergy between phenolics and dietary fiber may play a role in mediating amylase inhibition and therefore, have the potential to contribute to the management of type II Diabetes mellitus (Saito et al 1998;Toeller 1994). Chethan et al (2008a) studied the mode of inhibition of finger millet malt amylases by the millet phenolics and reported that the crude polyphenolic extract exerts mixed non-competitive type inhibition, whereas the individual phenolic compounds isolated from the extract exhibit uncompetitive inhibition.…”
Section: Inhibition Of Malt Amylases Pancreatic Amylase Intestinal mentioning
confidence: 99%
“…1 H and 13 C NMR spectra were measured on a BRUKER AVANCE II-400 (400 MHz) (Darmstadt, Germany) using DMSO-d 6 as solvent and TMS as internal standard. The elemental analysis was performed on a Costech Elemental Combustion System CHNS-O elemental analyzer (Valencia, CA).…”
Section: Chemistrymentioning
confidence: 99%
“…In the 1 H NMR spectra of these compounds, NH peaks were observed as a singlet at 13.75, 14.02 and 14.07 ppm, respectively 38 . The C ¼ S group resonated at 168.08-169.15 ppm in the 13 C NMR spectra of compounds (3a-c) and so their thionic form was proved 39 . Intramolecular cyclization of the acid hydrazide (1) with carbon disulfide in the presence of potassium hydrtoxide in .…”
mentioning
confidence: 95%
See 2 more Smart Citations